Attitudes Towards Police Use of Force - Palecek, Brady C.; Tryhus, Aaron M.; Goodman, Jeffrey A. (My University, 2017)
In the present study, we aim to shed light on this important social issue and see if there is a difference on how individuals view police use of force when we manipulate variables such as race/ethnicity and sex.
Color poster with text and graphs.
Keywords: Police brutality; African-Americans; Race; Police -- community relations; Posters